Effect of stimulation sites on the performance of electromagnetic middle ear implant: A finite element analysis. (September 2020) - Liu, Houguang; Wang, Wenbo; Zhao, Yu; Yang, Jianhua; Yang, Shanguo; Huang, Xinsheng; Liu, Wen
Abstract: Electromagnetic middle ear implants (MEIs), which use the mechanical vibration of their implanted transducers to treat hearing loss, have emerged to overcome the limitations of conventional hearing aids. Several reports have indicated that the electromagnetic MEI's performance changed with different stimulation sites of the transducer. The aim of this study was to analyze the influence of the transducers' stimulation sites on the electromagnetic MEIs' performance. To aid this investigation, a human ear finite-element model was developed from micro-CT images of an adult's right ear. The validity of the model was confirmed by comparing the model-derived results with experimental data. Then, stimulation forces, which simulate ideal electromagnetic transducers, were respectively applied at five typical coupling sites: the umbo, incus body, incus long process, the round window, and the stapes. The stimulation sites' influence on the electromagnetic MEI's performance was studied by analyzing their corresponding basilar membrane displacements. The results show that stimulation of the round window with a force produces more cochlear stimulation than equal force stimulation of the umbo, incus body, incus long process and the stapes, though the superiority of the round window depends on its smaller area compared to the stapes footplate. Among the forward stimulation, the stapes is the optimal stimulation site for the electromagnetic transducer regarding its hearing compensation's efficiency. The performance of the umbo stimulation is comparable to that of the incus-long-process stimulation. Driving the incus body is less efficient than stimulating the other forward driving sites. Additional, using the stapes response to evaluate the forward stimulation gives results similar to those deduced by the basilar membrane response; in contrast, for the round-window stimulation, the evaluation result based on the stapes response is prominently less than the one calculated by the basilar membrane response, especially in the mid-high frequency range. Highlights: A numerical model of the human ear with realistic anatomy was developed and verified. Stimulation sites significantly affect the hearing compensation performance. Stapes response is reliable for assessing the forward stimulation. Stapes response underestimates the round-window stimulation's performance." as last bullet point.